A Critical Discourse Analysis (CDA) of Marriott International Core Values - Rastitiati, Ni Kade Juli (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
The objective of the study is to explore the Marriott International Core Values through Critical Discourse Analysis. The data is taken from Marriott official website, and students’ interview. The data was then analyzed based on Fairclough’s three-dimensional model which covers text, discourse practice and social practice. The findings of the study highlight that Marriott’s core values have the power to motivate both management and associates to provide exceptional service to customers, the community, and the entire world. The core values benefit not only those inside Marriott's company but also the external stakeholders, especially its customers. This study underscores the significance of core values in shaping organizational culture and behavior. It implies that well-articulated core values can serve as a strategic tool to enhance employee engagement, customer satisfaction, and overall brand reputation. Organizations may adopt similar analytical approaches to assess and refine their core values, ensuring alignment with internal and external goals for sustainable growth and success.